2015
DOI: 10.4088/jcp.14m09092
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Features in Patients With a Major Depressive Episode

Abstract: Depressive mixed state, defined as the presence of 3 or more manic/hypomanic features, was present in around one-third of patients experiencing an MDE. The valid symptom, illness course and family history RBDC criteria we assessed identified 4 times more MDE patients as having mixed features and yielded statistically more robust associations with several illness characteristics of bipolar disorder than did DSM-5 criteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
157
3
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 151 publications
(174 citation statements)
references
References 0 publications
12
157
3
2
Order By: Relevance
“…[2][3][4][5][6][7][8][9][10][11][12] In MDD patients without mixed features, the presence of concurrent anxiety has been shown to reduce the likelihood of achieving an adequate antidepressant response. [19][20][21][22][23][24][25][26][27] We report here the results of a post-hoc analysis of a placebo-controlled, 6-week trial of MDD presenting with mixed features and anxiety which found that treatment with lurasidone significantly improved depressive symptoms in a subgroup of patients with moderate-to-severe anxiety at baseline.…”
Section: Lurasidone For Mdd With Mixed Features and Anxiety 241mentioning
confidence: 99%
See 3 more Smart Citations
“…[2][3][4][5][6][7][8][9][10][11][12] In MDD patients without mixed features, the presence of concurrent anxiety has been shown to reduce the likelihood of achieving an adequate antidepressant response. [19][20][21][22][23][24][25][26][27] We report here the results of a post-hoc analysis of a placebo-controlled, 6-week trial of MDD presenting with mixed features and anxiety which found that treatment with lurasidone significantly improved depressive symptoms in a subgroup of patients with moderate-to-severe anxiety at baseline.…”
Section: Lurasidone For Mdd With Mixed Features and Anxiety 241mentioning
confidence: 99%
“…1 The available evidence, largely from clinical study populations, suggests that major depressive disorder (MDD) with mixed features may occur in at least 25% of patients with major depression. [2][3][4][5][6][7][8][9][10][11][12] In patients with a diagnosis of MDD, the estimated lifetime prevalence of an anxiety disorder is greater than 35%. 13,14 The presence of comorbid anxiety in MDD has been found to be associated with greater illness severity, chronicity, and functional impairment.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…8 Prevalence estimates from clinical populations indicate that mixed features occur in at least 25% of patients with MDD. 11,14,[16][17][18][19][20][21][22] Irritability is not included as a criterion for mixed features in DSM-5, in part due to concerns regarding specificity. 8 Despite the prevalence and prognostic significance of irritability in MDD (with or without mixed features), few prospective studies have examined treatment response in this important clinical population.…”
Section: Introductionmentioning
confidence: 99%